Reconsideration of the primary and secondary diagnostic criteria of Meckel's diverticulum scintigraphy. A study of 93 confirmed cases - Wu, Ha; Zhao, Xiaofei; Li, Yiwei; Zhao, Ruifang (Hellenic journal of nuclear medicine, 2017)
Meckel's diverticulum scintigraphy (MDS) is a common method for diagnosing ectopic gastric mucosa (EGM), but atypical images are difficult to diagnose. This study aimed to improve the understanding of the existing diagnostic criteria through a review of confirmed cases. A total of 352 patients underwent MDS. Among 120 patients with a positive diagnosis, 106 underwent surgery. This study analyzed the imaging presentation, surgical records, and pathological results. The existing diagnostic criteria included the location, shape, and radioactive appearance of the lesions. Data from surgical records with typical or atypical images were compared. One hundred cases (100/106) were surgically confirmed to be Meckel's diverticulum (MD). The remaining 6 were intestinal polyps, intestinal duplication, duodenal ulcer, non-Hodgkin's lymphoma (NHL) and hiatal hernia. Out of the 100 MD cases, 93 had complete operation records and 59/93 of the MDS 63.4% MD were located in the right lower quadrant, and 81.7% had a round shape in the scintiscan. The onset of the lesions activity in 96.8% (90/93) of the cases corresponded with the onset of the gastric activity. The radioactivity of 97.8% (91/93) of the lesions gradually increased during the examination. There were no significant differences between the typical and atypical scintiscan images: in the distance of MD from the ileocecal valve, in the MD length, and the basal diameter of MD for lesions at different scintiscans (P>0.05), or of different shapes (P>0.05). Location in the right lower quadrant and round shape of the lesions are not the primary diagnostic factors for Meckel's diverticulum. The establishment of the diagnosis of MD requires careful consideration of other imaging characteristics such as: a) The onset of lesions' radioactivity to correspond with the onset of the gastric activity and b) The lesions' radioactivity to gradually increase during the scan procedure.